2022
DOI: 10.3390/nano12122020
|View full text |Cite
|
Sign up to set email alerts
|

Construction of α-MnO2 on Carbon Fibers Modified with Carbon Nanotubes for Ultrafast Flexible Supercapacitors in Ionic Liquid Electrolytes with Wide Voltage Windows

Abstract: In this study, α-MnO2 and Fe2O3 nanomaterials are prepared on a carbon fiber modified with carbon nanotubes to produce the nonbinder core–shell positive (α-MnO2@CNTs/CC) and negative (Fe2O3@CNTs/CC) electrodes that can be operated in a wide voltage window in ultrafast asymmetrical flexible supercapacitors. MnO2 and Fe2O3 have attracted wide research interests as electrode materials in energy storage applications because of the abundant natural resources, high theoretical specific capacities, environmental frie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Reproduced with permission. [68] Copyright 2022, MDPI. performance of IL-based material with bare MWCNTs and observed that IL enhances the device's performance by 85%.…”
Section: Ionic Liquid As Electrolytes For Cnts and Cnfs-based Scsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [68] Copyright 2022, MDPI. performance of IL-based material with bare MWCNTs and observed that IL enhances the device's performance by 85%.…”
Section: Ionic Liquid As Electrolytes For Cnts and Cnfs-based Scsmentioning
confidence: 99%
“…Further, at 298 K, a specific capacitance of 148 F g −1 and ED of 82 Wh kg −1 was obtained, and at 373 K, the obtained specific capacitance was 290 F g −1 with an ED of 161 Wh kg −1 . Li M. et al [ 68 ] fabricated α‐MnO 2 on CF‐modified CNT (α‐MnO 2 @CNTs/CNFs), which was used as positive and negative electrodes for SC. The electrode was prepared by chemical vapor deposition followed by the hydrothermal method as described in Figure a along with b unit cell and c crystal structure of α‐MnO 2 , and EMIMBF 4 was utilized as electrolyte.…”
Section: Ionic Liquids As Electrolytes In Carbon‐based Supercapacitor...mentioning
confidence: 99%
“…Specifically, the electric transformation from other energy forms is often stored in robust, reliable, and cost-effective energy storage devices such as lithium-ion, lithium-sulfur batteries, and sodium-ion batteries [14][15][16][17]. At present, the lithium-ion battery is the most widely used; however, due to the scarcity of the lithium element, the cost of lithium-ion batteries is increasing, which restricts their future development.…”
Section: Technological Innovation Of Sustainable Energymentioning
confidence: 99%
“…Based on their charge storage mechanism, supercapacitors are categorized into electric double-layer capacitors (EDLCs) and pseudocapacitors [9,10]. Carbon materials, with their excellent conductivity, stable chemical properties, high specific surface area, low cost, and mature processing technology, are considered high-quality electrode materials for EDLCs [11,12]. The electrode materials for pseudocapacitors mainly include metal oxides and conductive polymers [13,14].…”
Section: Introductionmentioning
confidence: 99%